Fiscal Rules, Financial Stability and Optimal Currency Areas - Paul De Grauwe; Pasquale Foresti (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper we suggest that Eurozone countries face a policy trade-off among: 1) a common rule imposing co-movements in fiscal policy; 2) financial stability; and 3) financial integration. We provide empirical evidence documenting the existence of such a trade-off in the period characterized by the financial crisis and by the sovereign debt crisis. Then, we conclude that the intense fiscal rules that have been introduced in the Eurozone after the emergence of the debt crisis reduced the capacity of national governments to deal with asymmetric shocks and became incompatible with either free capital mobility and/or financial stability.
Keywords: E44; E61; E62; 330; fiscal policy rules; Eurozone; financial stability; policy objectives; optimal currency areas.